Autopsy pathology : - Finkbeiner, Walter E. (Saunders/Elsevier, 2009)
The manual section covers basic and special autopsy procedures, biosafety, autopsy reports, death certificates, and other core subjects. Improved images provide a visual reference to performing, interpreting, and reporting post-mortem examinations. Pathologic findings are correlated with clinical causes. The photographs, many in color, depict common gross and microscopic autopsy findings. Templates for recording gross autopsy findings and describing traumatic injuries in forensic cases, and a guide to assessing growth and development are appended. Access to the online version of the text is available.